2020
DOI: 10.1016/j.sapharm.2019.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with comprehensive medication review completion rates: A national survey of community pharmacists

Abstract: Background Completion rates for medication therapy management (MTM) services have been lower than desired and the Centers for Medicare and Medicaid Services has added MTM comprehensive medication review (CMR) completion rates as a Part D plan star measure. Over half of plans utilize community pharmacists via contracts with MTM vendors. Objectives The primary objective of this survey study was to identify factors associated with the CMR completion rates of community pharmacies contracted with a national MTM ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Besides, rate between respondents and whole active CPs are similar to other surveys conducted among CPs 3 but inferior to others. 5 There is a lack of information, since Google Form does not allow to know the mean compilation time and the rate of interruptions during compilation, nor the authors could obtain data about the overall rate of response. However, the authors' purpose was to develop a brief and easy-to-compile questionnaire in order to obtain a large number of answers and avoid compiling interruption, and this objective has been achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, rate between respondents and whole active CPs are similar to other surveys conducted among CPs 3 but inferior to others. 5 There is a lack of information, since Google Form does not allow to know the mean compilation time and the rate of interruptions during compilation, nor the authors could obtain data about the overall rate of response. However, the authors' purpose was to develop a brief and easy-to-compile questionnaire in order to obtain a large number of answers and avoid compiling interruption, and this objective has been achieved.…”
Section: Discussionmentioning
confidence: 99%
“…2 Also, surveys have already been administered to community pharmacists (CPs) in order to assess their awareness on their role in COVID-19 crisis 3 and their preparedness and response to pandemic. 4,5 However, in Italy it is still unknown the impact of the virus outbreak on CPs, given the lack of data disclosed by Italian National Institute of Health statistics on this particular category of HCWs. Since the beginning of the pandemic, Italian community pharmacies and over-the-counter (OTC) drugstores have been considered as a primary service and therefore did not undergo lockdown, 6 thus increasing the risk of developing COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Only 3% of the global education spends is digital platform and by 2025 the digital spend will be $325 billion, which is less than 5% of the global education spend [35,36]. The present challenges faced by the government are the seamless delivery of education in the post-covidian direction of digital education, but this will be a far cure for the education disorders in the country [37]. The UGC is in the process of developing a game-changing policy where the universities that have a high 'NAAC' score among the top 100 NIRF rankings will be permitted to offer online programs.…”
Section: Digital Educationmentioning
confidence: 99%
“…The authors used several electronic tools to develop and deploy novel electronic data collection forms (i.e., e-forms/surveys) [4,[16][17][18][19][20][21][22][23]. In our experiences, we found that these 'e-form/survey' programs required little-to-no informatics training and were often accessible via desktop computers, tablets and other mobile devices alike.…”
Section: Electronic Form and Survey Softwarementioning
confidence: 99%